THE RAMSEY NUMBERS OF LINEAR FOREST VERSUS 3K3 2K4 - Sudarsan, I W.; Baskoro, E. T.; Assiyatun, H.; Uttunggadewa, S. (Journal of the Indonesian Mathematical Society, 2009)
"Pdf File"DOI :Â http://dx.doi.org/10.22342/jims.15.1.44.61-67